Are California venture capitalists the best venture capitalists? - Tyler Hull; Luna Y. Goldblatt (Cogent Economics & Finance)
We test if California VCs significantly outperform VCs from other US states. We additionally test in which instances California VCs outperform the other VC concentrated states of Massachusetts and New York. We find that VCs from California, Massachusetts, and New York have significantly greater probabilities of successfully exiting their investments than VCs from other states. Additionally, we show that California VCs are even more adept than VCs from Massachusetts and New York at 1. Early-stage investments, 2. Helping their entrepreneurial firms receive future rounds of financing, and 3. Helping their backed entrepreneurial firms receive higher IPO valuations and achieve superior post-IPO accounting ratios. Additional results suggest that VCs from California, Massachusetts, and New York are not only adept at selecting firms in which they invest in and continue to invest in, but they also enhance the value of the firms they select by means of monitoring their investments.